1991
DOI: 10.1084/jem.173.2.343
|View full text |Cite
|
Sign up to set email alerts
|

The mouse vitronectin receptor is a T cell activation antigen.

Abstract: ntegrins comprise a complex family of cell adhesion molecules involved in cell-cell and cell-extracellular matrix protein (ECMP)t interactions (1). At least three subfamilies have been defined on the basis of the association ofany of a number of at chains with a common /3 chain (2) . We have previously characterized two mAbs (H9.2B8 and 8.1802) that identified a novel integrin expressed on murine y/S and a//3 T cell lines and hybridomas as well as on T cells activated for prolonged periods of time (7-21 d) by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
1

Year Published

1992
1992
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(29 citation statements)
references
References 28 publications
2
26
1
Order By: Relevance
“…Moreover, integrin a v b 3 expression is upregulated on activated T cells [32], suggesting that integrin a v b 3 positively regulates immune responses at the interface between DC and T cells. Our present data showed that gp49B À/À DC can induce the proliferation of CD4 1 T cells better than that of CD8 1 T cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, integrin a v b 3 expression is upregulated on activated T cells [32], suggesting that integrin a v b 3 positively regulates immune responses at the interface between DC and T cells. Our present data showed that gp49B À/À DC can induce the proliferation of CD4 1 T cells better than that of CD8 1 T cells.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, gp49B contains two ITIM in its cytoplasmic portion, and inhibits activation signals upon cellular engagement with other activating receptors by recruiting SHP-1 to phosphotyrosylated ITIM [27,29]. gp49B binds to integrin a v and b 3 chains (a v b 3 ), which are expressed on a variety of cells including platelets, lymphocytes, and endothelial cells [30][31][32][33]. Colligation of gp49B with the highaffinity receptor for IgE or the type I FcgR by antibodies inhibits degranulation of mast cells or production of TNF-a by macrophages, respectively [29,34].…”
Section: Introductionmentioning
confidence: 99%
“…Several extracellular matrix proteins, including fibronectin, collagen, vitronectin, and laminin, have been shown to influence T cell functions by inducing T cell adhesion, motility, trafficking, and T cell coactivation (12)(13)(14). However, recent data using tenascin suggest that some matrix proteins can inhibit TCR-mediated T cell activation (15).…”
Section: Thrombospondin-1 Inhibits Tcr-mediated T Lymphocyte Early Acmentioning
confidence: 99%
“…Although gp49A has a short cytoplasmic tail that lacks any specific signaling motifs, gp49B contains two ITIMs in its cytoplasmic tail that mediate inhibition of cellular activation by recruiting SHP-1 and SHP-2 (26)(27)(28)(29). gp49B has been shown to bind to the integrin a v and b 3 (a v b 3 ), which is expressed on a variety of cells including activated T cells, and this interaction inhibits IgE-dependent degranulation of mast cells (30)(31)(32). Other studies showed that gp49B is also expressed on activated T cells and NK cells, and regulates IFN-g production (32)(33)(34).…”
mentioning
confidence: 99%